X2 T08 03 inequalities & graphs

649 views

Published on

Published in: Education, Technology
  • Be the first to comment

  • Be the first to like this

X2 T08 03 inequalities & graphs

  1. 1. Inequalities & Graphs
  2. 2. Inequalities & Graphs x2 e.g. i  Solve 1 x2
  3. 3. Inequalities & Graphs x2 e.g. i  Solve 1 x2
  4. 4. Inequalities & Graphs x2 e.g. i  Solve 1 x2
  5. 5. Inequalities & Graphs x2 e.g. i  Solve 1 x2
  6. 6. Inequalities & Graphs x2 e.g. i  Solve 1 x2 Oblique asymptote:
  7. 7. Inequalities & Graphs x2 e.g. i  Solve 1 x2  x2 4 x2 Oblique asymptote: x2 x2
  8. 8. Inequalities & Graphs x2 e.g. i  Solve 1 x2  x2 4 x2 Oblique asymptote: x2 x2
  9. 9. Inequalities & Graphs x2 e.g. i  Solve 1 x2  x2 4 x2 Oblique asymptote: x2 x2
  10. 10. Inequalities & Graphs x2 e.g. i  Solve 1 x2
  11. 11. Inequalities & Graphs x2 e.g. i  Solve 1 x2
  12. 12. Inequalities & Graphs x2 e.g. i  Solve 1 x2 x2 1 x2 x2  x  2 x2  x  2  0  x  2 x  1  0 x  2 or x  1
  13. 13. Inequalities & Graphs x2 e.g. i  Solve 1 x2 x2 1 x2 x2  x  2 x2  x  2  0  x  2 x  1  0 x  2 or x  1 x2 1 x2 x  2 or  1  x  2
  14. 14. (ii) (1990) Consider the graph y  x
  15. 15. (ii) (1990) Consider the graph y  x a) Show that the graph is increasing for all x  0
  16. 16. (ii) (1990) Consider the graph y  x a) Show that the graph is increasing for all x  0 dy Curve is increasing when 0 dx
  17. 17. (ii) (1990) Consider the graph y  x a) Show that the graph is increasing for all x  0 dy Curve is increasing when 0 dx y x dy 1  dx 2 x
  18. 18. (ii) (1990) Consider the graph y  x a) Show that the graph is increasing for all x  0 dy Curve is increasing when 0 dx y x dy 1  dx 2 x dy   0 for x  0 dx
  19. 19. (ii) (1990) Consider the graph y  x a) Show that the graph is increasing for all x  0 dy Curve is increasing when 0 dx y x at x  0, y  0 dy 1  dx 2 x dy   0 for x  0 dx
  20. 20. (ii) (1990) Consider the graph y  x a) Show that the graph is increasing for all x  0 dy Curve is increasing when 0 dx y x at x  0, y  0 dy 1 when x  0, y  0  dx 2 x dy   0 for x  0 dx
  21. 21. (ii) (1990) Consider the graph y  x a) Show that the graph is increasing for all x  0 dy Curve is increasing when 0 dx y x at x  0, y  0 dy 1 when x  0, y  0  dx 2 x dy   0 for x  0  curve is increasing for x  0 dx
  22. 22. b) Hence show that; n 2 1  2    n   xdx  n n 0 3
  23. 23. b) Hence show that; n 2 1  2    n   xdx  n n 0 3
  24. 24. b) Hence show that; n 2 1  2    n   xdx  n n 0 3 As x is increasing; Area outer rectangles  Area under curve
  25. 25. b) Hence show that; n 2 1  2    n   xdx  n n 0 3 As x is increasing; Area outer rectangles  Area under curve n 1  2    n   xdx 0
  26. 26. b) Hence show that; n 2 1  2    n   xdx  n n 0 3 As x is increasing; Area outer rectangles  Area under curve n 1  2    n   xdx 0 n 2 x x   3 0  2  n n 3
  27. 27. b) Hence show that; n 2 1  2    n   xdx  n n 0 3 As x is increasing; Area outer rectangles  Area under curve n 1  2    n   xdx 0 n 2 x x   3 0  2  n n 3 n 2  1  2    n   xdx  n n 0 3
  28. 28. c) Use mathematical induction to show that; 4n  3 1  2  n  n for all integers n  1 6
  29. 29. c) Use mathematical induction to show that; 4n  3 1  2  n  n for all integers n  1 6 Test: n = 1
  30. 30. c) Use mathematical induction to show that; 4n  3 1  2  n  n for all integers n  1 6 Test: n = 1 L.H .S  1 1
  31. 31. c) Use mathematical induction to show that; 4n  3 1 2  n  n for all integers n  1 6 Test: n = 1 41  3 L.H .S  1 R.H .S  1 6 1 7  6
  32. 32. c) Use mathematical induction to show that; 4n  3 1 2  n  n for all integers n  1 6 Test: n = 1 41  3 L.H .S  1 R.H .S  1 6 1 7  6  L.H .S  R.H .S
  33. 33. c) Use mathematical induction to show that; 4n  3 1 2  n  n for all integers n  1 6 Test: n = 1 41  3 L.H .S  1 R.H .S  1 6 1 7  6  L.H .S  R.H .S Hence the result is true for n = 1
  34. 34. c) Use mathematical induction to show that; 4n  3 1 2  n  n for all integers n  1 6 Test: n = 1 41  3 L.H .S  1 R.H .S  1 6 1 7  6  L.H .S  R.H .S Hence the result is true for n = 1 Assume the result is true for n  k where k is a positive integer
  35. 35. c) Use mathematical induction to show that; 4n  3 1 2  n  n for all integers n  1 6 Test: n = 1 41  3 L.H .S  1 R.H .S  1 6 1 7  6  L.H .S  R.H .S Hence the result is true for n = 1 Assume the result is true for n  k where k is a positive integer 4k  3 i.e. 1  2    k  k 6
  36. 36. c) Use mathematical induction to show that; 4n  3 1 2  n  n for all integers n  1 6 Test: n = 1 41  3 L.H .S  1 R.H .S  1 6 1 7  6  L.H .S  R.H .S Hence the result is true for n = 1 Assume the result is true for n  k where k is a positive integer 4k  3 i.e. 1  2    k  k 6 Prove the result is true for n  k  1
  37. 37. c) Use mathematical induction to show that; 4n  3 1 2  n  n for all integers n  1 6 Test: n = 1 41  3 L.H .S  1 R.H .S  1 6 1 7  6  L.H .S  R.H .S Hence the result is true for n = 1 Assume the result is true for n  k where k is a positive integer 4k  3 i.e. 1  2    k  k 6 Prove the result is true for n  k  1 4k  7 i.e. Prove 1  2    k  1  k 1 6
  38. 38. Proof:
  39. 39. Proof: 1  2  k 1  1  2  k  k 1
  40. 40. Proof: 1  2  k 1  1  2  k  k 1 4k  3  k  k 1 6
  41. 41. Proof: 1  2  k 1  1  2  k  k 1 4k  3  k  k 1 6 4k  3 k  6 k  1 2  6
  42. 42. Proof: 1  2  k 1  1  2  k  k 1 4k  3  k  k 1 6 4k  3 k  6 k  1 2  6 16k 3  24k 2  9k  6 k  1  6
  43. 43. Proof: 1  2  k 1  1  2  k  k 1 4k  3  k  k 1 6 4k  3 k  6 k  1 2  6 16k 3  24k 2  9k  6 k  1  6 k  116k 2  8k  1  1  6 k  1  6
  44. 44. Proof: 1  2  k 1  1  2  k  k 1 4k  3  k  k 1 6 4k  3 k  6 k  1 2  6 16k 3  24k 2  9k  6 k  1  6 k  116k 2  8k  1  1  6 k  1  6 k  14k  12  1  6 k  1  6
  45. 45. Proof: 1  2  k 1  1  2  k  k 1 4k  3  k  k 1 6 4k  3 k  6 k  1 2  6 16k 3  24k 2  9k  6 k  1  6 k  116k 2  8k  1  1  6 k  1  6 k  14k  12  1  6 k  1  6 k  14k  1  6 k  1 2  6
  46. 46. Proof: 1  2  k 1  1  2  k  k 1 4k  3  k  k 1 6 4k  3 k  6 k  1 2  6 16k 3  24k 2  9k  6 k  1  6 k  116k 2  8k  1  1  6 k  1  6 k  14k  12  1  6 k  1  6 k  14k  1  6 k  1 2  6 4k  1 k  1  6 k  1  6  4k  7  k  1 6
  47. 47. Hence the result is true for n = k +1 if it is also true for n =k
  48. 48. Hence the result is true for n = k +1 if it is also true for n =k Since the result is true for n = 1 then it is also true for n =1+1 i.e. n=2, and since the result is true for n = 2 then it is also true for n =2+1 i.e. n=3, and so on for all positive integral values of n
  49. 49. Hence the result is true for n = k +1 if it is also true for n =k Since the result is true for n = 1 then it is also true for n =1+1 i.e. n=2, and since the result is true for n = 2 then it is also true for n =2+1 i.e. n=3, and so on for all positive integral values of n d) Use b) and c) to estimate; 1  2    10000 to the nearest hundred
  50. 50. Hence the result is true for n = k +1 if it is also true for n =k Since the result is true for n = 1 then it is also true for n =1+1 i.e. n=2, and since the result is true for n = 2 then it is also true for n =2+1 i.e. n=3, and so on for all positive integral values of n d) Use b) and c) to estimate; 1  2    10000 to the nearest hundred 2 4n  3 n n  1 2  n  n 3 6
  51. 51. Hence the result is true for n = k +1 if it is also true for n =k Since the result is true for n = 1 then it is also true for n =1+1 i.e. n=2, and since the result is true for n = 2 then it is also true for n =2+1 i.e. n=3, and so on for all positive integral values of n d) Use b) and c) to estimate; 1  2    10000 to the nearest hundred 2 4n  3 n n  1 2  n  n 3 6 2 410000   3 10000 10000  1  2    10000  10000 3 6
  52. 52. Hence the result is true for n = k +1 if it is also true for n =k Since the result is true for n = 1 then it is also true for n =1+1 i.e. n=2, and since the result is true for n = 2 then it is also true for n =2+1 i.e. n=3, and so on for all positive integral values of n d) Use b) and c) to estimate; 1  2    10000 to the nearest hundred 2 4n  3 n n  1 2  n  n 3 6 2 410000   3 10000 10000  1  2    10000  10000 3 6 666700  1  2    10000  666700
  53. 53. Hence the result is true for n = k +1 if it is also true for n =k Since the result is true for n = 1 then it is also true for n =1+1 i.e. n=2, and since the result is true for n = 2 then it is also true for n =2+1 i.e. n=3, and so on for all positive integral values of n d) Use b) and c) to estimate; 1  2    10000 to the nearest hundred 2 4n  3 n n  1 2  n  n 3 6 2 410000   3 10000 10000  1  2    10000  10000 3 6 666700  1  2    10000  666700  1  2    10000  666700 to the nearest hundred
  54. 54. Hence the result is true for n = k +1 if it is also true for n =k Since the result is true for n = 1 then it is also true for n =1+1 i.e. n=2, and since the result is true for n = 2 then it is also true for n =2+1 i.e. n=3, and so on for all positive integral values of n d) Use b) and c) to estimate; 1  2    10000 to the nearest hundred 2 4n  3 n n  1 2  n  n 3 6 2 410000   3 10000 10000  1  2    10000  10000 3 6 666700  1  2    10000  666700  1  2    10000  666700 to the nearest hundred Exercise 10F

×